(untitled) (Palíndromo, 2015)
The comics-HQ are much more than an entertainment-related media; they have become, over the years, an important educational tool. This article presents a brief historical background of the origin of comic books and relates sequential art with the teaching of Visu- al Arts. Besides, this study supports the idea that the graphical analysis of dif- ferent genres of comics can contribute to the understanding of the process, the production of HQ in the classroom and for the stimulation of graphic de- velopment in children, during the stage of symbolic thought. The research was developed with students at a public municipal primary school in the city of Rio Grande/RS and presents results that point to the importance of the use of the HQ in creative processes, associated with drawing and writing; in promoting students ‘ interest by arts discipline; and graphic development.